Vitamin D3 encapsulated in brewer's spent yeast through vacuum biosorption: Studies on the sorption isotherm, release kinetics into the gastrointestinal system, and colon fermentation - Soares, Beatriz Caliman; de Jesus Costa, Tatielly; de Oliveira, Fellipe Lopes [UNESP]; Saliba, Ana Sofia; de Carvalho Balieiro, Júlio Cesar; Fukumasu, Heidge; Tulini, Fabricio Luiz; Sivieri, Katia [UNESP]; Alencar, Severino Matias; Favaro-Trindade, Carmen Sílvia (Elsevier, 2025)
Vitamin D3 is essential for bone health, immune system function, and overall well-being, but its deficiency remains a global health challenge. This study focused on encapsulating vitamin D3 with brewer's spent yeast biomass (BSY), both in natura and in plasmolyzed form, through vacuum biosorption followed by spray drying. This research examined several aspects, including sorption capacity, sorption isotherms through various mathematical models, the vitamin release profile of BSY via the INFOGEST protocol for simulated digestion, and the effects of colonic fermentation. The Redlich-Peterson and Freundlich mathematical models provided the best fit for the experimental data, indicating that physical sorption predominantly occurred on heterogeneous surfaces. When in vitro gastrointestinal simulations were tested, BSY particles effectively protected vitamin D3 during the oral and gastric phases, with a significant release (69.14 %) occurring in the intestinal phase, the site of absorption. Moreover, colonic fermentation assays demonstrated that the encapsulated vitamin D3 and BSY biomass positively influenced the gut microbiota, leading to an increase in beneficial bacterial genera such as Bacteroides. The production of short-chain fatty acids (SCFAs), particularly propionic acid 14.9 mmol/L and acetic acid 5.6 mmol/L, increased, highlighting the potential modulator of intestinal health.These findings emphasize the dual functionality of this system as both a delivery vehicle for vitamin D3 and a modulator of intestinal health, presenting a promising strategy for nutraceutical applications. The encapsulation process, which combines sustainability with efficacy, offers an innovative approach for addressing vitamin D deficiencies while simultaneously promoting gut health.